Analisis Validitas E-LKPD Fisika Berbasis Permainan Tradisional Boi-boian Materi Momentum dan Impuls - Ramadhani, Zalzabila; Suliyanah, Suliyanah (Pendidikan Fisika Universitas Nurul Huda, 2025)
This study aims to analyze the validity of a physics E-LKPD based on the traditional game boi-boian on momentum and impulse material. The research method used is Research and Development (R&D) with the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate), but it is limited to the development stage because the study focuses only on validity. The data collection instrument was a validation sheet given to three validators: two physics lecturers and one physic teacher. The validated aspects included material relevance, suitability of the E-LKPD with problem-solving skills, content feasibility, language, and appearance. The validation results showed an average score of 95.05%, categorized as very valid, indicating that the E-LKPD is suitable for use. This E-LKPD is recommended for further development and future research to analyze its practicality and effectiveness in improving students’ problem-solving abilities